Low-complexity 2D coherently distributed sources decoupled DOAs estimation method - Guo, XianSheng; Wan, Qun; Yang, WanLin; Lei, XueMei (Science China. Information sciences, 2009)
The existing directions-of-arrival （DOAs） estimation methods for two-dimensional （2D） coherently distributed sources need one- or two-dimensional search, and the computational complexities of them are high. In addition, most of them are designed for special angular signal distribution functions. As a result, their performances will degenerate when deal with different sources with different angular signal distribution functions or unknown angular signal distribution functions. In this paper, a low-complexity decoupled DOAs estimation method without searching using two parallel uniform linear arrays （ULAs） is proposed for coherently distributed sources, as well as a novel parameter matching method. It can resolve the problems mentioned above efficiently. Simulation results validate the effectiveness of our approach.